In Vitro Antimicrobial Activity of Various Cefoperazone/Sulbactam Products - Ming-Jen Sheu; Chi-Chung Chen; Ying-Chen Lu; Bo-An Su; Chun-Cheng Zhang; Shu-Shen Wang; Yin-Ching Chuang; Hung-Jen Tang; Chih-Cheng Lai (MDPI AG, 2020)
This study aims to assess the in vitro activity of different samples of cefoperazone/sulbactam (CFP/SUL) against multidrug-resistant organisms (MDROs). Clinical isolates of extended-spectrum β-lactamase (ESBL)-Escherichia coli, ESBL-Klebsiella pneumoniae, carbapenem-resistant Acinetobacter baumannii (CR-AB), and carbapenem-resistant Pseudomonas aeruginosa (CR-PA) were collected. The minimum inhibitory concentration (MIC) and time-killing methods were used to assess and compare the in vitro activities of different samples of cefoperazone/sulbactam (CFP/SUL) against these MDROs. For ESBL-E. coli, ESBL-K. pneumoniae, and CR-PA, product C had smaller variations than product A and B (p < 0.05). For CR-AB, product B had the largest variation compared to the other two products (p < 0.05). In the time-killing studies, significant differences among the products when used at 16/16 µg/mL were noted for ESBL-E. coli, ESBL-K. pneumoniae, and CR-AB isolates. In conclusion, this study demonstrated the significantly different activity of different products of CFP/SUL against MDROs.